Implementation of Warm Foot Soak Hydrotherapy Reduces the Risk of Indefective Peripheral Perfusion in Hypertension Patients in the Family - Dwi Uswatun Chasanah; Lis Nurhayati; Evy Tri Susanti (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Background: The risk of ineffective peripheral perfusion in hypertension occurs due to an increase in peripheral resistance due to a decrease in vascular elasticity, resulting in a decrease in blood circulation at the capillary level which can interfere with the body's metabolism. This can be controlled by non-pharmacological management by doing hydrotherapy with warm water foot soaks. This application will be successful by requiring the support of family members. Objective: To determine the application of warm foot immersion hydrotherapy to reduce the risk of ineffective peripheral perfusion in hypertensive patients in families. Methods: This study is a qualitative descriptive research with a case study strategy, using 2 participants, namely family members who experience hypertension in the family. The action is carried out 3 days for 15-20 minutes. Results: After hydrotherapy was carried out with warm water foot bath in both patients, the results were obtained in patient 1 the peripheral pulse strength was moderately increased radial pulse 84 x/min, brachial 82 x/min, posterior tibia 76 x/min, and dorsalis pedis 80 x/min, blood pressure decreased to 125/78 mmHg, mean arterial pressure decreased to 88, and CRT improved to < 2 seconds. Patient 2 obtained the results of a moderate increase in peripheral pulse strength of 84 x radial pulse / minute, brachial 80 x / minute , posterior tibia 68 x / minute, and dorsalis pedis 70 x / minute, blood pressure decreased to 130/79 mmHg, average arterial pressure decreased to 96, and CRT improved to < 2 seconds. Family members are able to apply warm water foot soak hydrotherapy to lower the risk of ineffective peripheral perfusion in hypertensive patients. Conclusions: Warm foot immersion hydrotherapy may lower the risk of ineffective peripheral perfusion in hypertensive patients in families.